Screening of Indigenous Microorganisms as Potential Biofertilisers for Periurban Horticulture Areas - Querejeta, Giselle Andrea (2020)
In Buenos Aires periurban area, horticultural practices are one of the most important activities. Pesticides and fertilisers are used without any control to cover the farmers´ needs, obtaining high crop yields at short terms and modifying soil ecosystem in the long term. The aim of this work was to isolate indigenous strains from periurban horticultural units with pesticide degrading capacity and to evaluate their plant growth-promoting properties in order to design biofertilisers to be applied in the restoration of these exploited soils. After the screening, eight strains were isolated and identified. They showed not only the capacity to produce indole-3- acetic acid, to fix nitrogen, to secrete siderophores and to solubilise calcium phosphate but also tolerated the mixture of pesticides usually used for horticultural practices. By their behaviour in mixed cultures and plant growth-promoting properties, these autochthonous isolates represent a promising alternative as biofertilisers according to soil type and activity.